Evaluasi dampak penggunaan teknologi terkini dalam mufrodat bahasa Arab di Madrasah - Sopiyana, Hilma Ro’ipatus (Maliki Interdisciplinary Journal, 2024)
This study aims to evaluate the impact of using the latest technology in learning Arabic mufrodat (vocabulary). This study uses qualitative research methods with an analytical descriptive approach. Data were collected through direct observation, interviews, and literature study. The subjects of this study were 10th grade students of MAN 1 Blitar. The results show that the use of the latest technology, such as smart phone applications, online learning software, and e-learning platforms, has had a significant impact in improving the efficiency and effectiveness of learning Arabic mufrodat. The application of technology in learning Arabic mufrodat has provided flexibility for learners to learn anytime and anywhere. In addition, various interactive features in e-learning applications and platforms have enriched the learning experience, motivated students, and improved vocabulary retention. However, challenges such as technology accessibility, digital content quality and technology dependency also need to be addressed. This research provides a better understanding of how the use of current technology can enhance the learning of Arabic mufrodat. The implications of the findings can help with curriculum development, lesson design, and the use of technology in the context of Arabic language education. In addition, this study also provides directions for further research in this area.